Reinterpretation of Ethic Value in Minangkabau’s Superstition - Ulya, Ridha Hasnul (TELL - US JOURNAL, 2018)
This article aims to reveal reinterpretation ethic value of Minangkabau’s superstition especially in the society of Kubuang Tigo Baleh’s superstition. Besides the concepts of superstition, superstition in well-mannered culture and superstition pattern of the society of Kubuang Tigo Baleh are explained. There are four patterns of superstition, namely negative, positive, prediction and witchcraft pattern. However, in the process of pattern meaning the lofty ethic values are framed and considered as local wisdom of the society in Kubuang Tigo Baleh which is appropriate, well-mannered, educated and existence acknowledged as a belief.